Study of serum non-HDL cholesterol in cerebrovascular disease (Bangladesh Journal of Medical Science, 2010)
Background: Non-HDL cholesterol is a potential newer risk factor for cerebrovascular diseases (CVD). Objective: To explore the association of non-HDL cholesterol with cerebrovascular disease. Methods: This case control study was carried out in the Department of Biochemistry, BSMMU, Dhaka during the period of January to December 2007 to evaluate the association of non-HDL cholesterol with CVD in Bangladeshi population. A total number of 135 subjects of both sexes were grouped as Group-I (CVD cases) and Group-II (Healthy controls). Group-I include 85 cases of which 59 were ischaemic cerebrovascular diseases (ICVD) and 26 were haemorrhagic cerebrovascular diseases (HCVD). By taking the history and doing clinical examination and laboratory investigations, diabetes mellitus, malignant disease, renal disease, liver disease and diuretic medication were excluded from study subjects. Serum non-HDL cholesterol was measured in all study subjects. Statistical analysis was performed by using SPSS for windows version 12.0. Mean values of the findings were compared between groups. One way ANOVA test and multiple comparison (Bonferroni‘t’) test were used to see the level of significance. Results: Serum non-HDL cholesterol found significantly increased in CVD, ICVD and HCVD cases in comparison to control subjects. But ICVD and HCVD cases did not differ with respect to serum non-HDLcholesterol. Conclusion: The result shows that elevated non-HDL cholesterol is associated with CVD. Prospective study with large sample size is required to evaluate the elevated Non-HDL cholesterol as a risk factor of CVD. Key words: Non-HDL cholesterol; Cerebrovascular disease; Ischaemic cerebrovascular disease; Haemorrhagic cerebrovascular disease. DOI: 10.3329/bjms.v9i3.6469Bangladesh Journal of Medical Science Vol.09 No.3 July 2010, pp.143-149